Risk factors associated with intermediate and long-term mortality following vascular surgery in South African patients - Biccard, BM (Clinics Cardive Publishing, 2010)
SUMMARY: There are few data on predictors of mortality following vascular surgery in South African patients. While in the developed world, peri-operative risk factors are also associated with intermediate-term survival, it is likely that the weighting and even the clinical risk factors may be different in South African patients due to the epidemiology of cardiovascular disease in developing countries. The aim of this study was therefore to determine risk factors associated with intermediate and long-term mortality in South African vascular surgical patients. DESIGN: A retrospective cohort study was conducted. Intermediate and long-term survival was determined by subsequent hospital visits or admissions. For patients who did not return to the hospital, the patient or patient’s next of kin was contacted telephonically. The outcome of the patient, and the time to the outcome following the surgical procedure were recorded. Bivariate and multivariate analysis was conducted using Cox regression analysis to determine predictors of intermediate-term mortality. RESULTS: Only hypertension and diabetes were associated with intermediate and long-term mortality at the bivariate level of analysis with p < 0.10. There was no co-linearity between hypertension and diabetes. Hypertension was the only predictor of intermediate and long-term survival retained in the multivariate model (hazard ratio 3.86, 95% confidence interval 0.83–15.4, p = 0.086). CONCLUSION: In contrast to developed-world observations, peri-operative clinical risk indices were not associated with intermediate and long-term survival in South African vascular surgical patients. Instead, two risk factors that were identified in the South African National Burden of Disease study were associated with mortality. It appears that a ‘western lifestyle’ (and the presence of associated risk factors) may be more important predictors of intermediate and long-term mortality than peri-operative risk predictors of cardiac events in South African vascular surgical patients. This study highlights an important public health issue for the South African population where the most important determinants of mortality are continued exposure to risk factors (such as hypertension and diabetes) in the community, with little modification of these risk factors through primary health surveillance and management, even after surgical admission for pathology known to be associated with these risk factors.